Case report: Detection of anti-bullous pemphigoid antigen 180 antibodies in a patient with Behçet’s disease - Didona, Dario; Sequeira Santos, Antonio Manuel; Cunha, Tomas; Hinterseher, Julia; Kussini, Jacqueline; Hertl, Michael (Frontiers in Medicine, 2022)
Behçet’s disease (BD) is a systemic inflammatory disease of unknown etiology. BD is characterized by relapsing oral and genital ulcers, several different cutaneous features, relapsing bilateral uveitis, and involvement of internal organs, showing vascular, gastrointestinal, and neurological manifestations. Serologically, BD is not characterized by disease-specific autoantibodies. In fact, only laboratory markers of inflammation, such as C-reactive protein, may be increased in association with increased disease activity. Bullous pemphigoid (BP) is an autoimmune disease characterized mainly by tense blisters and urticaria-like plaques on the skin. In addition, BP can involve oral mucosa in up to 20% of patients. Patients with BP show serum IgG autoantibodies against BP antigen 180 (BP180) and/or BP antigen 230 (BP230). Tissue-bound autoantibodies can be visualized as linear IgG staining along the basement membrane by direct immunofluorescence microscopy. In this report, we first described a young patient with BD who showed IgG autoantibodies against BP180 without developing blisters or urticaria-like plaques.